Assortative interactions revealed in a fission–fusion society of Australian humpback dolphins. (12th March 2019) - Hunt, Tim N; Allen, Simon J; Bejder, Lars; Parra, Guido J
Abstract: Understanding individual interactions within a community or population provides valuable insight into its social system, ecology, and, ultimately, resilience against external stimuli. Here, we used photo-identification data, generalized affiliation indices, and social network analyses to investigate dyadic relationships, assortative interactions, and social clustering in the Australian humpback dolphin ( Sousa sahulensis ). Boat-based surveys were conducted between May 2013 and October 2015 around the North West Cape, Western Australia. Our results indicated a fission–fusion society, characterized by nonrandom dyadic relationships. Assortative interactions were identified both within and between sexes and were higher among members of the same sex, indicating same-sex preferred affiliations and sexual segregation. Assortative interactions by geographic locations were also identified, but with no evidence of distinct social communities or clusters or affiliations based on residency patterns. We noted high residency among females. Models of temporal patterns of association demonstrated variable levels of stability, including stable (preferred companionships) and fluid (casual acquaintances) associations. We also demonstrated some social avoidance. Our results point to greater social complexity than previously recognized for humpback dolphins and, along with knowledge of population size and habitat use, provide the necessary baseline upon which to assess the influence of increasing human activities on this endemic, Vulnerable species. Abstract : The extent and nature of interactions between males and females has a profound influence on animal social structures. Here, we show that Australian humpback dolphins live in a dynamic, fission–fusion society, characterized by nonrandom and strong same-sex preferred associations. Our results suggest greater social complexity than previously recognized for humpback dolphins and provide the necessary baseline for assessing human impacts on the social structure of this threatened species.